Решить тригонометрическое уравнение:

Регина56797 Регина56797    2   12.07.2019 03:00    0

Ответы
kadieva1976 kadieva1976  18.09.2020 07:21
Функция косинус четная, поэтому
cos( \frac{ \pi }{6}-2x)=cos(2x- \frac{ \pi }{6})

Решаем уравнение:
cos(2x- \frac{ \pi }{6}) =-1 \\ \\ 2x- \frac{ \pi }{6}= \pi + 2\pi n,n\in Z \\ \\ 2x= \frac{ \pi }{6}+ \pi +2 \pi n,n\in Z \\ \\ 2x= \frac{7 \pi }{6} +2 \pi n,n\in Z \\ \\ x= \frac{7 \pi }{12} + \pi n,n\in Z
ПОКАЗАТЬ ОТВЕТЫ
alenaefremova79 alenaefremova79  18.09.2020 07:21
Другие вопросы по теме Алгебра